(untitled) ("Journal "U". Economy. Management. Finance.", 2021)
Every year more and more Russian enterprises do not fulfill their obligations, which often leads to their liquidation. In order to avoid such a situation, it is very important to regularly and timely diagnose the state of the enterprise at risk. This article presents some ways to diagnose business in a crisis and unstable economy.